Association of ambient PM2.5 and its components with preeclampsia risk among pregnant women in a high-altitude region - Rui Li; Zhenjuan Li; Hanping Ma; Donghua Li; Xiong Yue; Xiaoshu Zhang; Tingrong Wang; Zixuan Zou; Tianshan Shi; Xiaowei Ren (Environmental Pollution, 2026)

A machine-vision based seedling replenishing system for pepper plug seedling transplanter - Meng Chen; Yang Xu; Changjie Han; Panpan Yuan; Zhai Shi; Jia You; Desheng Li; Xu Ma; Hanping Mao (Computers and Electronics in Agriculture, 2026)

Design and experiment of a ridge-surface based cutting height active adjustment system for a leafy vegetable harvester - Haitao Peng; Zhiyu Zuo; Guoxin Ma; Luhua Han; Ze Liu; Hanping Mao (Biosystems Engineering, 2025)

Effects of structure and soil parameters on the detection performance of a contact soil surface height detection device - Haitao Peng; Hanping Mao; Mohamed Farag Taha; Luhua Han; Zhiyu Zuo; Guoxin Ma (Computers and Electronics in Agriculture, 2025)

Associations of ambient air pollution exposure to fine particulate matter and its chemical constituents before and during pregnancy with the risk of full-term small for gestational age: a retrospective cohort study - Tingrong Wang; Hanping Ma; Rui Li; Donghua Li; Tianshan Shi; Zhenjuan Li; Zixuan Zou; Xiaowei Ren (International Archives of Occupational and Environmental Health, 2025)

The role of exogenous hydrogen sulfide in mitigating cadmium toxicity in plants: A comprehensive meta-analysis - Hanping Cao; Kejin Song; Yingying Hu; Qingxiao Li; Tengfei Ma; Rui Li; Nan Chen; Shunqin Zhu; Wanhong Liu (Environmental Science and Pollution Research, 2024)

Urban greenspaces and child blood pressure in China: Evidence from a large population-based cohort study - Wen-Wen Bao; Nan Jiang; Yu Zhao; Boyi Yang; Gongbo Chen; Yinqi Pu; Hanping Ma; Jinghong Liang; Xiang Xiao; Yuming Guo; Guanghui Dong; Yajun Chen (Environmental Research, 2024)

Prenatal exposure to fine particulate matter chemical constituents and the risk of stillbirth and the mediating role of pregnancy complications: A cohort study - Tianshan Shi; Hanping Ma; Donghua Li; Li Pan; Tingrong Wang; Rui Li; Xiaowei Ren (Chemosphere, 2024)

Preparation of carbon nanotubes by catalytic pyrolysis of dechlorinated PVC - Wanli Ma; Yuting Zhu; Ning Cai; Xianhua Wang; Yingquan Chen; Haiping Yang; Hanping Chen (Waste Management, 2023)

Ensemble learning system to identify nutritional risk and malnutrition in cancer patients without weight loss information - Liangyu Yin; Jie Liu; Ming Liu; Jin Zheng; Aiguo Xu; Quanjun Lyu; Yongdong Feng; Zengqing Guo; Hu Ma; Jipeng Li; Zhikang Chen; Hui Wang; et al. (Science China Life Sciences, 2023)

Effects of Different Temperatures on the Antibacterial, Immune and Growth Performance of Crucian Carp Epidermal Mucus - Bin Wang; Guoxin Ma; Yong Liu; Yafei Wang; Xiaoxue Du; Qiang Shi; Hanping Mao (Fishes, 2021)
Fish is one of the important sources of energy and protein, and proper water temperature is key to successful fish breeding. The authors of this study evaluated crucian carp growth, mucus antibacterial properties, and immune indicators at 17, 21, 24, 27, and 31 °C. The results indicated that in the range of 17–31 °C, the resistance of epidermal mucus to Vibrio harveyi decreased with temperature rising. At 24 and 27 °C, the activities of lysozyme and catalase significantly increased; alkaline phosphatase activity, superoxide dismutase activity, and total protein concentration first increased and then decreased with rising temperature; the highest values were observed at 24 °C, with increases of 56.55%, 26.64%, and 44.52%, respectively, compared to those under the 17 °C treatment. When the treatment reached 27 °C, the temperature had an effect on the growth and antibacterial properties of crucian carp, and the activities of alkaline phosphatase and superoxide dismutase were significantly reduced. At temperatures of 17–24 °C, the survival rate of crucian carp could reach more than 93%, and at the temperature of 24 °C, the specific growth rate reached the highest value of 43.29%. Therefore, the most favorable temperature for the long-term breeding of crucian carp was found to be 24 °C. This study provides a favorable experimental basis for the establishment of intelligent aquaculture systems and the setting of water environment parameters.